Appraisal of space words and allocation of emotion words in bodily space. - Fernando Marmolejo-Ramos (Public Library of Science (PLoS), 2013)
The body-specificity hypothesis (BSH) predicts that right-handers and left-handers allocate positive and negative concepts differently on the horizontal plane, i.e., while left-handers allocate negative concepts on the right-hand side of their bodily space, right-handers allocate such concepts to the left-hand side. Similar research shows that people, in general, tend to allocate positive and negative concepts in upper and lower areas, respectively, in relation to the vertical plane. Further research shows a higher salience of the vertical plane over the horizontal plane in the performance of sensorimotor tasks. The aim of the paper is to examine whether there should be a dominance of the vertical plane over the horizontal plane, not only at a sensorimotor level but also at a conceptual level. In Experiment 1, various participants from diverse linguistic backgrounds were asked to rate the words "up", "down", "left", and "right". In Experiment 2, right-handed participants from two linguistic backgrounds were asked to allocate emotion words into a square grid divided into four boxes of equal areas. Results suggest that the vertical plane is more salient than the horizontal plane regarding the allocation of emotion words and positively-valenced words were placed in upper locations whereas negatively-valenced words were placed in lower locations. Together, the results lend support to the BSH while also suggesting a higher saliency of the vertical plane over the horizontal plane in the allocation of valenced words.